Laparoscopic surgery for two patients with strangulated transomental hernias - Yuka Fujimoto; Yuki Ohya; Shintaro Hayashida; Masayoshi Iizaka; Yuto Maeda; Sayahito Kumamoto; Akira Tsuji; Hidekatsu Shibata; Kunitaka Kuramoto; Hironori Hayashi; Osamu Nakahara; Shinjiro Tomiyasu; et al. (Surgical Case Reports)
Abstract Background Transomental hernias are a rare type of internal hernia. We report two cases of successful cases of laparoscopic repair. One required laparotomy due to concern for intestinal viability. Case presentation The first patient was a 67-year-old man who presented with abdominal pain and vomiting. He had no history of laparotomy or abdominal injury. Computed tomography suggested small bowel obstruction and possible intestinal strangulation. Emergent laparoscopy found approximately 200 cm of small bowel was strangulated around the greater omentum. The strangulation was released laparoscopically, but because of the color of the strangulated bowel, laparotomy was performed to evaluate viability. The involved portion of intestine was not resected. The patient experienced transient postoperative paralytic ileus and was discharged on postoperative day 14. The second patient was a 56-year-old man who presented with abdominal pain. Abdominal computed tomography revealed dilatation of the small intestine and a closed loop suggesting ileus due to intestinal strangulation. An emergency laparoscopy found a transomental hernia, and the strangulation was released laparoscopically. Recovery was uneventful, and the patient was discharged on postoperative day 6. Conclusion Transomental hernia can be successfully treated laparoscopically. In cases where bowel viability is a concern, laparotomy should not be hesitated.